MBKM Kesmas Report by Design FKM Unair at PT. Garuda Maintenance Facility Aeroasia TBK - Nandha Chinintya Lukiswara Hariyanto; Tri Martiana (Jurnal Indonesia Sosial Sains, 2025)
The MBKM Kesmas by Design program bridges theoretical knowledge and practical OSH implementation at PT GMF AeroAsia Tbk., an aviation maintenance facility with high-risk operations. Objectives: This study aims to (1) identify hazards in scrap area grinding/manual handling, (2) assess risks via HIRADC analysis, and (3) propose targeted controls. Field observations, worker interviews, and risk evaluations were conducted, aligned with the hierarchy of control (elimination to PPE). The study identified 15 grinding hazards (e.g., sparks, vibration) and 6 manual handling risks (e.g., overload injuries), with high-risk activities (e.g., severed hands, back injuries) requiring engineering/administrative interventions. Post-control, residual risks were reduced to low/moderate levels. The program demonstrates how academic-industry collaboration can enhance OSH practices, urging adoption of digital hazard monitoring and standardized documentation. Findings are scalable to high-risk industries globally.